Russia and Germany Reborn : Unification, the Soviet Collapse, and the New Europe. - Stent, Angela (Princeton University Press, 2001)
The relationship between Russia and Germany has been pivotal in some of the most fateful events of the twentieth century: the two World Wars, the Cold War, and the emergence of a new Europe from the ashes of communism. This is the first book to examine the recent evolution of that tense and often violent relationship from both the Russian and German perspectives. Angela Stent combines interviews with key international figures--including Mikhail Gorbachev--with insights gleaned from newly declassified archives in East Germany and her own profound understanding of Russian-German relations. She p.